Peran Mahasiswa Dalam Konsultasi Keuangan Untuk Peningkatan Laporan Keuangan UMKM Es Iso Lego - Febriyanti Artika Putri; Ziyadatul Khoiroh; Bagas Widianto Saputra; Anas Ramdani Putra Kurnaedi; Muhammad Iqbal Ainur Rohman (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the preparation of financial statements in Micro, Small and Medium Enterprises (MSMEs) that experience profits. This research uses a descriptive qualitative approach with a case study method. The results showed that MSMEs experienced difficulties in preparing financial reports in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The main obstacle is the limited thinking about managing financial statements and the inadequate number of Human Resources (HR) in preparing financial reports. This research also shows that MSMEs that have not prepared financial statements in accordance with SAK EMKM still use simple accounting methods, such as only recording petty cash receipts and expenditures. Therefore, this study recommends the implementation of SAK EMKM to facilitate MSMEs in preparing financial reports in accordance with applicable standards.